(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
The underwear fit and pressure comfort is a crucial importance. This paper firstly used the Untouched 3D Body Scanner to scan the 110 young female body, and extracts a total of 17 human body sizes related to underwear structure, in all the directions including the horizontal directionvertical direction and other direction. Through analyzing the data, this paper focused on that among the horizontal dimensions: waist circumference, abdomen circumference, hip circumference, and the thigh root circumference; Vertical dimension: height, waist high; and other size: lower trunk length is the biggest difference, and the key part that affects the underwear specification. To analyze these measurement results and contrast with the national female underwear shape series standard found that the most common is the intermediate of A shape, at present, so regard the female intermediates as main object of study. Assess this knitting fabric is suitable for the middle of elastic underwear, through the test of fabric gram weight, warp ⁄ weft, thickness and elasticity. Moreover, this paper made the zero relaxation prototype with inelastic fabric by utilized vertical cutting and pattern, combined with young women wearing preferences, chose the female low-rise boxer briefs style as the main style of study. On this basis increase to -4 cm relaxation in turn in the Abdominal girth, hip girth and thigh girth, fork reduce 0.5 cm in turn. According to this regular to make five different relaxation knitted female underwear, and invites eight eligible subjects to put on the underwear to complete a series of dynamic testing, at the same time, gives the subjective evaluation timely for each related panties pressure comfort under the condition of different actions. Finally, With local comfortable stress evaluation method to evaluate the pressure when subjective human movement, the biggest impact of the site in turn, is abdominal, back hip, thigh, the bottom fork, based on analyzing the data, found that when abdomen circumference and hip circumference of the loose quantity is -17 cm, thigh circumference is -12 cm, and fork is 13 cm, people who wear this kind of knitted underwear can have the most comfortable feeling.